EZH2 Regulates Protein Stability via Recruiting USP7 to Mediate Neuronal Gene Expression in Cancer Cells - Lei, Anhua; Chen, Lu; Zhang, Min; Yang, Xiaoli; Xu, Liyang; Cao, Ning; Zhang, Zan; Cao, Ying (Frontiers in Genetics, 2019)
Misexpression of chromatin modification factors and changed epigenetic modifications play crucial roles for tumorigenesis. Our previous studies demonstrated that inhibition of epigenetic modification enzymes EZH2, LSD1, DNMTs and HDACs caused post-mitotic neuron-like differentiation in different cancer cells. However, how they regulate neuronal differentiation in cancer cells was unknown. Here, we show that EZH2, LSD1, DNMT1 and HDAC1 form interactions themselves, meanwhile, they also interact with SMAD proteins and β-CATENIN in cancer cells. Chemical inhibition of these enzymes leads to reduced level of proteins except HDAC1. The change in protein level and/or enzymatic activities further result in changed chromatin modifications on neuronal gene promoters, and activation of neuronal genes. Inhibition of these enzymes in neural progenitor cells also caused neuronal differentiation, similar to cancer cells. Particularly, EZH2 interacts with and required for the stability of LSD1, HDAC1, DNMT1, β-CATENIN or SMAD2/4, via recruitment of deubiquitinase USP7. Reduced EZH2 leads to enhanced ubiquitination and degradation of these proteins, and decreased binding of LSD1, HDAC1 and DNMT1 to neuronal gene promoters, and lessened Wnt and TGFβ target gene activation. Hence, EZH2 sustains a series of proteins that promote tumorigenesis, in addition to its original function of histone methylation. Considering together with other studies, we conclude that these chromatin modification factors function in the same way in cancer cells as in neural progenitor/stem cells. The similarity between cancer cells and neural progenitor/stem cells provides an insight into the essence and unified framework for cancer initiation and progression, and are suggestive for novel strategies of cancer therapy.